Cytidine deaminase deficiency in mice enhances genetic instability but limits the number of chemically induced colon tumors. (28th February 2023) - Onclercq-Delic, Rosine; Buhagiar-Labarchède, Géraldine; Leboucher, Sophie; Larcher, Thibaut; Ledevin, Mireille; Machon, Christelle; Guitton, Jérôme; Amor-Guéret, Mounira
Abstract: Cytidine deaminase (CDA) catalyzes the deamination of cytidine (C) and deoxycytidine (dC) to uridine and deoxyuridine, respectively. We recently showed that CDA deficiency leads to genomic instability, a hallmark of cancers. We therefore investigated whether constitutive CDA inactivation conferred a predisposition to cancer development. We developed a novel mouse model of Cda deficiency by generating Cda- knockout mice. Cda +/+ and Cda −/− mice did not differ in lifetime phenotypic or behavioral characteristics, or in the frequency or type of spontaneous cancers. However, the frequency of chemically induced tumors in the colon was significantly lower in Cda −/− mice. An analysis of primary kidney cells from Cda −/− mice revealed an excess of C and dC associated with significantly higher frequencies of sister chromatid exchange and ultrafine anaphase bridges and lower Parp-1 activity than in Cda +/+ cells. Our results suggest that, despite inducing genetic instability, an absence of Cda limits the number of chemically induced tumors. These results raise questions about whether a decrease in basal Parp-1 activity can protect against inflammation-driven tumorigenesis; we discuss our findings in light of published data for the Parp-1-deficient mouse model. Highlights: We developed a novel mouse model of cytidine deaminase (Cda) deficiency ( Cda −/− ). Cda deficiency results in cellular genetic instability and lower PARP-1 activity. Cda deficiency does not increase the risk of spontaneous cancers. Cda deficiency decreases the risk of chemically-induced tumors. Lower PARP-1 activity may reduce inflammation-driven tumorigenesis in Cda −/− mice.